Study of retention and infiltration wells as a result of resettlement of the Batang Kuranji upper watershed. Issue 1 (January 2021) - Ophiyandri, T; Istijono, B; Gromiko, A; Hidayat, B; Junaidi,; Nulrajabmil,
Abstract: Padang City is one of the metropolitan cities in West Sumatra Province and has six (6) watersheds, one of which is the Batang Kuranji watershed. Over the last few years Batang Kuranji watershed has experienced significant infrastructure and urban development which began with the massive earthquake of 30 September, 2009 with coastal communities, afraid of being affected by larger aftershocks having the potential of a tsunami, moving to the upper watershed. As a result, the type of land cover that was originally an infiltration area has been changing into a runoff area. The Batang Kuranji channel with a discharge (Q25) 870 m 3 /s may not be able to accommodate the change in discharge which can lead to flooding. This paper aims to determine changes in discharge that occur due to changes in land cover and to analyse whether the use infiltration wells and retention pond can reduce the flooding volume. Two methods to calculate runoff discharge were adopted, HEC-HMS 4.1 Modelling and Nakayasu. It was found that the peak discharged increases to (Q25) 1, 037.60 m 3 /s. Thus, creating retention pond with a dimension of 35 hectare with a depth of 5 m and 34, 246 infiltration wells can reduce the flood risk. The percentage of runoff discharge they can accommodate is 90.98% and 9.02% respectively.